Media Sosial sebagai Agen Transformasi Politik: Analisis Pengaruh terhadap Proses Komunikasi Politik - Arsyad Arsyad; Rifma Ghulam Dzaljad; Mia Nurmiarani; Safutra Rantona (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
The development of social media has transformed the paradigm of political communication, opening the door for active participation of the community in political discussions. This research aims to delve into the changes in the dynamics of political communication alongside the proliferation of social media and reveal its impact on the formation of public opinion. The research employs a literature review approach to detail, evaluate, and summarize literature related to political communication, social media, and the role of digital platforms. Conceptual analysis and identification of previous research methodologies are utilized to establish the theoretical and methodological foundation. The results indicate that social media, as an agent of change, empowers the community in political discourse and shapes public opinion. This research integrates three communication theories (Agenda Setting, Gatekeeping, and Uses and Gratifications) to understand the complexity of political transformation through social media. In conclusion, social media creates fundamental changes in political communication, necessitating a deep understanding by political actors to optimize positive impacts while minimizing risks. This research is expected to contribute to the understanding of the complex dynamics between political communication and social media in the digital era.